Relative Abundance and Yield Loss Assessment of Lentil Aphid, Aphis craccivora Koch in Relation to Different Sowing Dates - Hossain, Md. Altaf; Ferdous, Jannatul; Salim, MMR (Journal of Agriculture & Rural Development, 2008)
Relative abundance of lentil aphid, Aphis craccivora Koch were investigated and yield loss assessment at different sowing dates during rabi season of 1999-2000 and 2000-2001 at Ishurdi Bangladesh. Lentil aphid appeared in field in the first week of January. The maximum aphid population (15.82/twig) was recorded in the first week of February 2000-2001, but the population reached to the peak was in the last week of January in 1999-2000, subsequently rainfall caused a sudden reduction of aphid population in latter dates. Aphid population and infestation increased with the delayed dates of sowing. The crop sown in November received less aphid infestation and consequently produced higher yield than the crop sown in December. During 1999-2000, the avoidable yield loss due to aphid infestation was recorded 0.90 to 6.78% and in 2000-2001 it was 2.65 to 9.00% depending on the different dates of sowing. Avoidable yield loss was less in November sowing crop than the crop sown in December. On the other hand, yield increased by 0.91 to 7.27% and 2.72 to 9.89% in 1999-2000 and 2000-2001 respectively, due to protection measures taken against aphids and this was also depend on different dates of sowing. Key words: Lentil aphid, delayed sowing, infestation, yield.